QuillBot as a Digital Writing Tool: An Analysis of Writing Improvement and the Development of Beginner Writers - Nurdelia Nasution; Meisya Audreyanna Azzahra; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Beginner students often face difficulties in academic writing, such as organizing ideas, choosing correct grammar, and expressing information in their own words. Because of this, many students use QuillBot as a writing support tool. This study aims to understand how QuillBot helps beginner writers become more independent in academic writing. The research used a mixed-method approach with 30 students from the English Language and Literature Department at the State University of Medan, with data collected through a Likert-scale questionnaire and open-ended reflections. The findings show that more than 70% of the students use QuillBot frequently in their writing tasks. Most students said that QuillBot helps improve grammar accuracy, sentence clarity, and paraphrasing skills, and also increases their confidence in writing. The summarizing feature also helps students identify and restate main ideas. However, 59% of the students noted that using QuillBot too much may reduce creativity and lead to dependency. The study concludes that QuillBot is helpful as a supporting tool for writing, but it should be used in balance. Students still need to practice writing independently so they can develop their own writing style and confidence.